Signalling and Expressive Interaction: Online News Users' Different Modes of Interaction on Digital Platforms. Issue 4 (20th April 2020) - Sang, Yoonmo; Lee, Jee Young; Park, Sora; Fisher, Caroline; Fuller, Glen
Abstract: Online news users interact with news on digital platforms in different ways. Some take advantage of the technical affordances that allow sharing, liking and commenting, while others do not. Based on a national survey of the Australian adult online news users, this study explores online news users' different modes of interaction on digital platforms: non-interaction, signalling interaction, and expressive interaction. This study demonstrates that different types of online news users are largely determined by a combination of structural influences and individual factors related to the uptake, reception, and dissemination of news. This study contributes to the growing body of literature on news engagement by exploring the concept of interaction as a more specific term to describe online news behaviours, and identifies different types of news users connected to, rather than disembodied from, their practice. In doing so, this article advances the understanding of news consumption behaviour and its implications for engaging news audiences in the digital age.